Zika virus infection in Malaysia: an epidemiological, clinical and virological analysis - Woon, Yuan Liang; Lim, Mei Fong; Tg Abd Rashid, Tg Rogayah; Thayan, Ravindran; Chidambaram, Suresh Kumar; Syed Abdul Rahim, Syed Sharizman; Mudin, Rose Nani; Sivasampu, Sheamini (BMC infectious diseases, 2019)
Background A major outbreak of the Zika virus (ZIKV) has been reported in Brazil in 2015. Since then, it spread further to other countries in the Americas and resulted in declaration of the Public Health Emergency of International Concern (PHEIC) by World Health Organization. In 2016, Singapore reported its first minor ZIKV epidemic. Malaysia shares similar ecological environment as Brazil and Singapore which may also favor ZIKV transmission. However, no ZIKV outbreak has been reported in Malaysia to date. This study aimed to discuss all confirmed ZIKV cases captured under Malaysia ZIKV surveillance system after declaration of the PHEIC; and explore why Malaysia did not suffer a similar ZIKV outbreak as the other two countries. Methods This was an observational study reviewing all confirmed ZIKV cases detected in Malaysia through the ZIKV clinical surveillance and Flavivirus laboratory surveillance between June 2015 and December 2017. All basic demographic characteristics, co-morbidities, clinical, laboratory and outcome data of the confirmed ZIKV cases were collected from the source documents. Results Only eight out of 4043 cases tested positive for ZIKV infection during that period. The median age of infected patients was 48.6 years and majority was Chinese. Two of the subjects were pregnant. The median interval between the onset of disease and the first detection of ZIKV Ribonucleic Acid (RNA) in body fluid was 3 days. Six cases had ZIKV RNA detected in both serum and urine samples. Phylogenetic analysis suggests that isolates from the 7 cases of ZIKV infection came from two clusters, both of which were local circulating strains. Conclusion Despite similar ecological background characteristics, Malaysia was not as affected by the recent ZIKV outbreak compared to Brazil and Singapore. This could be related to pre-existing immunity against ZIKV in this population, which developed after the first introduction of the ZIKV in Malaysia decades ago. A serosurvey to determine the seroprevalence of ZIKV in Malaysia was carried out in 2017. The differences in circulating ZIKV strains could be another reason as to why Malaysia seemed to be protected from an outbreak.